Assessment of Psychopathology and Quality of Life in Children and Adolescents With Migraine - Oztop, Didem Behice; Tasdelen, Bedia Ince; PoyrazogLu, Hatice Gamze; Ozsoy, Saliha; Yilmaz, Rabia; Sahin, Nilfer; Bozkurt, Selma (Sage Publications Inc, 2016)
Aim: The aims of this study were to investigate comorbid psychiatric disorders and to identify anxiety and depression levels and quality of life in children and adolescents with migraine; and to assess their relationship with migraine. Method: 35 patients aged 9-16 years were followed in our neurology clinic and their parents were included into the study. 35 age- and sex-matched patients were employed as the control group. In the subjects included, psychiatric disorders were assessed by using the Schedule for Affective Disorders and Schizophrenia for School Age Children-Present and Lifetime Version. All children and adolescents were assessed by using the Children's Depression Inventory, the State-Trait Anxiety Inventory and the Pediatric Quality of Life Inventory. In addition, the Pediatric Migraine Disability Assessment Tool and visual analog scale were used to identify the degree of disability and pain severity in patients with migraine. Findings: In the psychiatric assessment of children and adolescents with migraine, it was found that a psychiatric diagnosis was made in 40% of patients; and depression scale scores were significantly higher than those of controls. Quality of life was found to be poorer in patients with migraine compared to controls. It was found that quality of life was negatively correlated with pain severity and degree of disability; while it was positively correlated with depression scores. Discussion: In children and adolescents with migraine, treatment of psychiatric disorders in addition to migraine therapy can facilitate migraine management and may decrease the need for prophylactic therapy.
Keywords: migraine; psychopathology; quality of life; child; adolescent